The Influence of Perceived Usefulness and Cashback Reward Program Mediated by E-wallet Engagement on E-wallet User Satisfaction - Nurmalasari, Nurmalasari; Afifah, Nur; Mustaruddin, Mustaruddin (Widya Cipta: Jurnal Sekretari dan Manajemen, 2025)
The rapid growth of digital payment systems has made e-wallets increasingly important in the financial technology sector. This study examines the influence of perceived usefulness and cashback reward programs on e-wallet user satisfaction, with e-wallet engagement as a mediating variable. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS) approach, data were collected from 300 e-wallet users through purposive sampling. The results indicate that perceived usefulness (β=0.137, p<0.05) and cashback reward programs (β=0.236, p<0.001) significantly influence e-wallet engagement. E-wallet engagement significantly affects user satisfaction (β=0.287, p<0.001), and perceived usefulness directly influences satisfaction (β=0.362, p<0.001). The mediation analysis reveals that e-wallet engagement partially mediates the relationship between both independent variables and user satisfaction. The findings suggest that e-wallet providers should focus on enhancing perceived usefulness and designing attractive reward programs while maintaining high user engagement to drive satisfaction.